Study on water and soil quality parameters of shrimp and prawn farming in the southwest region of Bangladesh - Zafar, MA; Haque, MM; Aziz, MSB; Alam, MM (Journal of the Bangladesh Agricultural University, 2016)
Water and soil quality parameters play a vital role for sustainable shrimp and prawn production which together is the leading exportable seafood product in Bangladesh contributing to a significant amount of foreign currency earnings. However, this sector is often negatively criticized by the consumers of importing countries for farm (locally called gher in Bengali) environment. In this context, an investigation was carried out to assess water and soil quality parameters of shrimp and prawn farms in southwest Bangladesh. This study was conducted at Dumuria and Paickgacha Upazila of Khulna district during dry and wet season in 2012. The data were collected from 9 shrimp and prawn farms and they were categorized in three different groups (as treatments) including 3 prawn (T1), 3 shrimp & prawn (T2) and 3 shrimp farms (T3). Water temperature, dissolved oxygen, pH, ammonia, nitrate, nitrite, alkalinity, salinity, total phosphorous and total hardness were measured using portable advanced HACH water quality test kit in both dry and wet season. Farm soil (sediment) quality parameters including pH, organic carbon, total nitrogen and available phosphorus were measured in the laboratory in wet season. It was found that most of the water quality parameters were in suitable range in both seasons for prawn, shrimp & prawn and shrimp farming. However, the ammonia content was 0.009 to 0.45 ppm and 0.2 to 0.6 ppm in shrimp farm during dry and wet season, respectively which was higher than the other category of farms. The higher ammonia content in shrimp farm might be due to the decomposition of aquatic weeds, organic matter, uneaten feed etc. creating stress to shrimp. Different co-relationships found between the water quality parameters in all the farming systems in the both seasons. In terms of soil quality parameters such as pH, organic carbon and total nitrogen, there was no significant difference between the farm categories. However, available phosphorous content was significantly higher in shrimp & prawn farm. Phosphorous content was found negatively correlated with pH and organic carbon content of farm sediment (soil). From the present study, it could be argued that ammonia is the main problem for shrimp farms that may cause severe disease outbreak which need to be addressed from the view point of research and development towards sustainable seafood production in Bangladesh. J. Bangladesh Agril. Univ. 13(1): 153-160, June 2015